Implementation of Gender Equality in Schools - Endah Ratnawaty Chotim (GoAcademica Research & Publishing, 2022)
Schools are critical institutions for transforming students' perspectives, especially gender-biased actions. Thus, gender-neutral schools that serve a strategic role and function in educating pupils for their multi-intelligence grow effectively without being bound by often gender-biased social beliefs. One of education's objectives is to teach students how to establish a just society free of gender discrimination. However, in practice, overcoming discrimination in education needs a number of measures, one of which is developing an education system based on gender equality. This study uses a qualitative approach with descriptive methods in presenting data analysis. The study results show that gender equality in education is still ongoing in Indonesia due to the patriarchal culture and the stigma that women do not need to get higher education because, in the end, they will become housewives and raise children. Therefore, to implement justice and gender equality in the school sector, it is necessary to pay attention to several factors such as human resource capacity, capacity building, school culture, and partnership networks. In conclusion, gender equality in schools can be implemented through gender-responsive learning, lesson planning, classroom arrangement, language use, and gender-based classroom interaction.